Alcohol consumption is falling, but is it enough?. Issue 18 (19th September 2015) - Chaplin, Steve
<x xml:space="preserve">Abstract</x> Data from the Health and Social Care Information Centre show a fall in alcohol consumption in England, particularly among younger people. This leaves the UK sitting somewhere in the middle of EU states with the highest consumption figures at 10.6 litres per person